Challenges faced by Farmer Producer Organisations (FPOs) - A Review - Shree, D. A. Nithya; Shree, P. Vaishnavi (Journal of Agricultural Extension Management, 2022)
Farmer Producer Organizations (FPOs) provide small farmers with endto-end support and services, including technical assistance, marketing, processing, and cultivation inputs. Small Farmers' Agribusiness Consortium is the nodal agency in India which promotes FPOs. A Farmer Producer Organization plays an important role in promoting and strengthening member-based institutions of farmers. The major goal is to provide producers with a higher income by forming their own organization. FPOs which are formed as Farmer Producer Companies (FPCs) allow members to access financial and other input services. To compete with other companies and competitors in the market, FPCs must be competent with other companies and competitors in the market, and they have a tremendous potential to capture future food retails not only in India but throughout the world. In this connection around 5000 FPOs have started functioning throughout the country; among these some are functioning effectively and some are not. In this regard, there is a need to find out the constraints faced by the FPOs in effective functioning. Keeping this in view an attempt has been made in this review based paper to highlight various constraints related to the growth, performance and challenges of FPOs along with strategies to make them more effective in the present context. The major constraints found based on the review are lack of sufficient finance, lack of proper government price policy, lack of awareness of credit facilities, lack of connection with financial organizations and lack of proper market information